MEETING THE EMPLOYMENT NEEDS OF MARGINALIZED YOUTH: A REVIEW OF PROMISING YOUTH EMPLOYMENT PROGRAMS - Youmans, Alexandra; Hussain, Alicia; Godden, Lorraine; Kutsyuruba, Benjamin; Butler, Alana; DeLuca, Christopher; Shewchuk, Samantha (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
The Youth Job Connection program in Ontario, Canada is designed to help multi-barriered youth transition into the workforce. As part of an evaluation of the program, a review of comparable employment programs in Canada and similar English-speaking countries was conducted, which involved 57 national and 36 international programs. The purpose of the review was to identify promising programs and explore how they support the successful transition of NEET (not in education, employment, or training) youth into the labour market. A major finding was that promising youth employment programs not only address the work needs of marginalized youth, but also life skills and life stabilization. Such programs incorporate pre-employment training, mentoring and job coaching, paid work placements, life skills training, and life stabilization supports. Life stabilization supports varied across programs, with different amounts and types offered; further research is needed to determine what life stabilization supports best help NEET youth to secure and maintain employment. Considerations for improving the quality of employment programs for NEET youth are discussed. Lastly, given that NEET youth are not a homogeneous group, youth employment programs should target subpopulations of NEET youth, like those that are marginalized.